Efektivitas Game Pejuang Hadits dalam Meningkatkan Pemahaman Siswa MAN 2 Karawang - Hafizduddin Hafizduddin; Iqbal Amar Muzaki; Abdul Kosim (Indo-MathEdu Intellectuals Journal, 2023)
The background of this research is the low understanding of students in knowing the hadiths which are quite popular so it is necessary to find a way to improve students' understanding of hadith. Besides that, many students take their time to play games that are less useful. Therefore, this study analyzes the ability of students to recognize hadith, especially the hadith about remembrance and adab because these two things can be done by students in everyday life. This study uses descriptive qualitative methods to describe the results of observations and draw conclusions. This research is presented in narrative form to present the findings found in the field. The results of this study indicate that the use of educational games such as the game Pejuang Hadits can increase students' understanding of hadith, especially the hadith about remembrance and etiquette so that the game is quite effective for use to students in order to introduce students to authentic hadiths. In addition, the game Pejuang Hadith attracts students to play while learning in a more interactive way. So it is hoped that the results of using this Hadith Fighter game will result in a better student understanding